Self-assembly strategy to obtain phytic acid doped OBN hybrids for enhancing fire safety of epoxy resin with lower dielectric loss. (November 2022) - Feng, Tingting; Cui, Jiahui; Wang, Yaxuan; Piao, Junxiu; Wang, Yaofei; Ren, Jinyong; Guan, Haocun; Lian, Richeng; Ou, Mingyu; Liu, Lei; Chen, Xilei; Jiao, Chuanmei
Abstract: The further application of epoxy resin (EP) is limited by its brittleness and flammable characteristics determined by its structure. For the sake of solving this problem, the OBN-P-PA hybrid is designed, which is obtained by self-assembly of hydroxyl boron nitride (OBN), polyethyleneimine (PEI), and phytic acid (PA) based on electrostatic interaction, and then introduced into EP. Through thermogravimetric analysis (TGA) of pure EP and its composites under N2 atmosphere, it is concluded that the OBN-P-PA hybrid promotes carbonization and improves the thermal stability of EP. Besides, when 4 wt% OBN-P-PA hybrid is added to EP, the peak heat release rate (pHRR), smoke factor (SF), and peak carbon monoxide production rate (pCOPR) decrease by 40.1%, 45.3%, and 39.7% with higher glass transition temperature ( T g ) and flexural modulus, respectively, compared with those of neat EP. The results suggest that the OBN-P-PA hybrid can effectively restrain the release of heat and smoke in the combustion process and further improve the fire safety of EP. Dielectric properties tests exhibit that the OBN-P-PA hybrid contributes to reducing the dielectric loss of EP. The above results demonstrate that EP/OBN-P-PA composite has infinite potential in electronics. Graphical abstract: Image 1 Highlights: Based on electrostatic interaction, OBN–P-PA are constructed by self-assembly of OBN (-), PEI (+) and PA (-). The introduction of phytic acid significantly improves the interface interaction between OBN and EP. After adding 4 wt% of OBN-P-PA hybrids, the fire safety performance of epoxy resin composites is obviously enhanced.